Hubungan Parental Attachment dengan Subjective Well-Being Anak Broken Home - Hazhara, Ifra Fadilla; Firman, Firman (ANWARUL, 2024)
This research is motivated by children from broken homes due to their parents' divorce, which impacts children in terms of happiness, decision-making confusion, emotional stability, the demand to adjust to different parenting styles received, and the lack of parental support during developmental transitions. The impact on broken home children can be minimized by enhancing individual subjective well-being. One way to enhance subjective well-being is through parental attachment. This study aims to determine the relationship between parental attachment and subjective well-being among broken home students at SMP N 34 Padang. The research uses a quantitative method with a correlational study type. The population in this study consists of 60 broken home students from grades VII and VIII for the 2023/2024 academic year at SMP N 34 Padang, using Total Sampling technique. Data collection was carried out using a parental attachment questionnaire and a subjective well-being questionnaire for broken home students. The data were processed using descriptive analysis techniques and Pearson product-moment correlation analysis with the help of SPSS version 20.0 for Windows. The results of this study indicate that (1) the parental attachment of broken home students is in the medium category with a percentage of 73.3%, (2) the subjective well-being of broken home students is in the high category with a percentage of 50.0%, and (3) there is a significant relationship between parental attachment and subjective well-being in broken home students, with a correlation value (r) of 0.692 and a significance level of <0.000, indicating a high level of relationship. Based on these research findings, guidance and counseling services that can be provided to enhance parental attachment and subjective well-being in broken home students include information services, individual counseling services, and group counseling services.